Bergaptol, a Major Furocoumarin in Citrus: Pharmacological Properties and Toxicity - Pakkapong Phucharoenrak; Dunyaporn Trachootham (Molecules, 2024)
Bergaptol (5-hydroxypsoralen or 5-hydroxyfuranocoumarin) is a naturally occurring furanocoumarin widely found in citrus fruits, which has multiple health benefits. Nonetheless, no specific review articles on bergaptol have been published. Compiling updated information on bergaptol is crucial in guiding future research direction and application. The present review focuses on the research evidence related to the pharmacological properties and toxicity of bergaptol. Bergaptol has anti-inflammatory, antioxidant, anti-cancer, anti-osteoporosis, anti-microbial, and anti-lipidemic effects. It can inhibit the activities of cytochrome P450s (CYP), especially CYP2C9 and CYP3A4, thereby affecting the metabolism and concentrations of some drugs and toxins. Compared with other coumarins, bergaptol has the least potency to inhibit CYP3A4 in cancer cells. Instead, it can suppress drug efflux transporters, such as P-glycoprotein, thereby overcoming chemotherapeutic drug resistance. Furthermore, bergaptol has antimicrobial effects with a high potential for inhibition of quorum sensing. In vivo, bergaptol can be retained in plasma for longer than other coumarins. Nevertheless, its toxicity has not been clearly reported. In vitro study suggests that, unlike most furocoumarins, bergaptol is not phototoxic or photomutagenic. Existing research on bergaptol has mostly been conducted in vitro. Further in vivo and clinical studies are warranted to identify the safe and effective doses of bergaptol for its multimodal application.